The effectiveness of applying the accrual basis of accounting in the public sector in the Kingdom of Saudi Arabia - Al-Garni, Jameelh Mohammed; Al-Sayegh, Maha Faisal (Journal of Economic, Administrative and Legal Sciences, 2023)
The aim of this research is to study the effectiveness of applying the accrual basis of accounting in the public sector in the Kingdom of Saudi Arabia. Particularly, its impact on developing the performance of financial departments, achieving strategic goals to improve the quality of financial accounts in the government sector, and enhancing the principle of transparency. The study population is the government agencies that were selected at the initial stage of applying the accrual basis in the Kingdom of Saudi Arabia. The study sample is represented by the Ministry of Environment, Water and Agriculture and its national centers (National Center for Meteorology, National Center for Environmental Compliance Control, National Center for Vegetation Cover and Combating Desertification).The reason for choosing this ministry is because it is one of the important ministries that contains a large number of activities, in addition to the diversity of financial departments in each activity and the accounting and accounting interests in each affiliated center. The questionnaire was used as a tool for collecting data, as it was distributed to (60) employees from the Financial Management Department, where their job titles and positions vary from auditors, accountants and financial managers. Results of the study showed that the transition to the accrual basis of accounting helps in providing financial reports that are characterized by honest representation of the phenomena to be disclosed in the government entity, and the application of the accrual basis of accounting contributes to the existence of control procedures to ensure the correctness and integrity of the processing of financial data and raise the efficiency of performance Financial and administrative in the public sectors.